Sistem Pengendalian Persediaan Bahan Baku dalam Menunjang Efektivitas Proses Produksi : Studi Kasus pada PT X. - Muktiadji, Nusa; Hidayat, Lukman (Jurnal Ilmiah Ranggagading (JIR), 2006)
Raw material inventory control comprises of quality and physical control to keep the raw material saves from any disturbance. Therefore, company is necessary to direct raw material inventory control sufficiently, that start from requisites planning and acquisition stage, unloading, storage, safeguarding, and bringing out for the benefit of producing process up to product manufacturing finished. The finding of study showed that the company has implemented control system of raw material inventory in its producing process. The company has implemented raw material inventory control system by planning and supervising of raw material necessities in accordance with determined necessities by the company. Keywords: Production Management; raw material inventory